(3GdGdJRGe HGdVeGf ai YbhO GdHfGA hGdJTjjO (B: s (3OQGSI JWHjbjI Ydi YbhO GdGfTGAGJ GdOhdjI (B/ s - (3YeQh Wg HOhi eMeO Ydis; (3Ydi MSjf fLjOIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2004)
(3JJfGhd gPg GdOQGSI (B: (3ehVhY GdGdJRGe HGdVeGf ai YbhO GdHfGA hGdJTjjO OQGSI JWHjbjI Ydi YbhO GdGfTGAGJ GdOhdjI (B: (3MjK JYQV GdVeGfGJ GdbGfhfjI ai YbhO GdHfGA hGdJTjjO hgi ai SHjd Pdc JYQV GdVeGf GdYTQi (B: (3hGdVeGfGJ GdeSJMOKI ai GdbGfhf GdaQfSi HbGfhf (B4 (3jfGjQ SfI (B1978 : (3hGdeJeKdI ai VeGf caGAI GdGOGA Gh GfJXGe GdYed (B: (3hVeGf JeGe GdGfLGR Gh eG jYQa HGdVeGf GdSfhis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2004s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B601-634s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3YbhO GdGfTGAGJ GdOhdjIs; (3YbhO GdHfGA hGdJTjjOs; (3fehPL GdajOcs; (3Gdeaghe GdbGfhfj ddJSdjes; (3QH GdYed s; (3WQb GdJSdes; (3GdJMcjes; (3GdbGfhf GdaQfSjs; (3SdWGJ GdegfOSs; (3GdVeGf GdYTQjs; (3OYhj GdVeGfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs